Differences in Activity Profiles During Action Time: A Comparison Between Winners and Losers in Young Male Silat Tempur Athletes - Shapie, Muhamad Nizam Mohamad; Akbar, Muhammad Farid Chairul; Samsudin, Hazim; Al-Syurgawi, Dahlia; Rahim, Mohamad Rahizam Abdul; Abdullah, Nagoor Meeara; Parnabas, Vincent; Nawai, Nasru Syazwan; Kusrin, Jamiaton; Bakar, Noridah Abu; Nor, Mohad Anizu Mohd (International Martial Arts and Culture Journal, 2023)
Background and aim. Match analysis has been widely used to examine performance characteristics and activity demands in combat sports. However, empirical evidence focusing on Silat Tempur, particularly among youth athletes, remains limited. This study aimed to analyse and compare the activity profile during action time between winners and losers in national Silat Tempur competitions involving young male athletes.Methods.  Seven publicly available video recordings of official national Silat Tempur matches from different weight categories were analysed using a validated notational analysis system. Each match was observed twice with a 48-hour interval. Intra-observer reliability demonstrated excellent agreement for total actions and outcome variables (ICC ≥ 0.95). A matched-samples t-test was used to compare activity profiles between winners and losers.Results.  The results showed that hit target (HT) outcomes accounted for the highest proportion of actions (50.6%), followed by hit elsewhere (HE) (32.5%) and miss opponent (MO) (16.9%). Winners performed a greater number of total actions (79 actions, 51%) compared to losers (57 actions, 41%). In addition, winners recorded a substantially higher proportion of hit target outcomes (48 actions, 69%) than losers (21 actions, 31%). These findings indicate that hit target outcomes were the primary determinant of match success, as they directly contributed to scoring in Silat Tempur. Overall, winners demonstrated a higher frequency of effective actions, accounting for 79 of the 136 total actions recorded during the matches.Conclusions.      Performance differences in youth Silat Tempur competitions are primarily determined by the effectiveness of actions rather than the total volume of actions performed. These findings provide empirical evidence on the activity profile of youth Silat Tempur and offer practical insights for training design that emphasises scoring effectiveness and balanced offensive–defensive strategies.